DETERMINAN STUNTING PADA BALITA BERDASARKAN STATUS IMUNISASI DAN ASI EKSKLUSIF DI WILAYAH KERJA PUSKESMAS TILANGO KABUPATEN GORONTALO - Kilo, Ervina; Modjo, Dewi; Sudirman, Andi Akifa (JURNAL KEPERAWATAN, 2024)
Background :Stunting has an impact on individuals, families, communities and countries. The individual impact of stunting includes, among other things, causing brain growth disorders which can result in permanent disruption of brain function. Stunting occurs due to many factors, including immunization status and exclusive breastfeeding. Aim :The aim of the research is to analyze stunting in toddlers based on immunization status and exclusive breastfeeding. Methods :Research methods quantitative design with a cross sectional approach. The population was 1,361 toddlers with a sample size of 93 toddlers. Results :The results showed the highest basic immunization status was complete, namely complete, 81 people, the highest exclusive breastfeeding, namely 76 people were given exclusive breastfeeding, and the highest incidence of stunting, namely not stunting (normal), 72 people and 21 toddlers experienced stunting, between the incidence of stunting and the immunization status obtained. The value of p value=0.000<0.05 and the incidence of stunting with exclusive breastfeeding was obtained by the value of p value=0.000<0.05. Conclusion :There is a relationship between stunting in toddlers based on immunization status and exclusive breastfeeding in Tilango Health Center.